2016
DOI: 10.1111/and.12618
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between volume of the seminal vesicles and sexual activity in middle-aged men

Abstract: The relationship between volume of the seminal vesicles and the frequency of sex and sexual function in middle-aged men is not clear. This study included 81 patients who were diagnosed with localized prostate cancer. Volume of the seminal vesicles was examined using a volume analyser from computed tomography. Sexual function was subjectively evaluated using the Expanded Prostate Cancer Index Composite and Erection Hardness Score. The frequency of sex was surveyed using our original questionnaire. The mean ± SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
(29 reference statements)
1
5
1
Order By: Relevance
“…In this study, the volume of the seminal vesicles was not found to be correlated with sexual desire or erectile function, although in a previous study the volume of the seminal vesicles did reflect sexual function (Taniguchi et al, ). That study, however, included patients who were taking silodosin for benign prostate hyperplasia.…”
Section: Discussioncontrasting
confidence: 65%
“…In this study, the volume of the seminal vesicles was not found to be correlated with sexual desire or erectile function, although in a previous study the volume of the seminal vesicles did reflect sexual function (Taniguchi et al, ). That study, however, included patients who were taking silodosin for benign prostate hyperplasia.…”
Section: Discussioncontrasting
confidence: 65%
“…These differences could be explained by the fact that our rats got DM just for short time than other studies [ 10 , 11 , 26 ]. Lager seminal vesical may be related to higher sexual activity was reported in the human study [ 27 ]. A similar finding was also reported in a study by Birkhauser et al [ 28 ], showing that mice with larger seminal vesicles had a remarkably higher intromission rate than mice with smaller seminal vesicles.…”
Section: Discussionmentioning
confidence: 78%
“…Body composition changes were independent of normal growth as tibia length was not altered by FOLFOX treatment (Table 1). Seminal vesicle mass is considered an indirect marker of male gonadal function 40,41 . At four cycles of FOLFOX treatment seminal vesicle mass was reduced (−21%), which returned to PBS values at 10 weeks recovery (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Seminal vesicle mass is considered an indirect marker of male gonadal function. 40,41 At four cycles of FOLFOX treatment seminal vesicle mass was reduced (−21%), which returned to PBS values at 10 weeks recovery (Table 1). Spleen mass is commonly elevated under conditions of increased inflammation.…”
Section: Physical Function and Body Composition After Long-term Recov...mentioning
confidence: 94%